Relationship troubles at the mitochondrial level and what it might mean for human disease - Rachel James (Open Biology)
Understanding and treating disease depend upon our knowledge of how the body works. The biomedical approach to disease describes health purely in terms of biological factors, with a focus on the genome as the molecular basis for cellular function and dysfunction in disease. However, the eukaryotic cell has evolved as a partnership between prokaryotic cells with mitochondria being crucial to this relationship. Aside from their role as bioenergetic and biosynthetic hubs, mitochondria are also involved in cell signalling and cell fate pathways, playing a multifaceted role in cell function and health. Crucially, mitochondria are implicated in most diseases. Perhaps then, visualizing biomedical function on the backdrop of endosymbiosis may provide another viewpoint for explaining and treating disease.